The effects of image resolution and exposure duration on facial beauty and ugliness evaluationsOSF - Takanori Sano; Mika Gondo; Yuna Osaka; Hideaki Kawabata (Acta Psychologica)
The beauty or ugliness of a face is affected by factors such as the resolution of the face image presented on the screen and its exposure duration. The present study investigated the effects of image resolution and exposure duration on the beauty and ugliness evaluations of face images processed with down-sampling and Gaussian blurring. We prepared two types of face images with these blur processing treatments and conducted two experiments to evaluate beauty and ugliness perceptions at various exposure durations. The data were analyzed using linear mixed models. We found that in both cases of blurring, the more the blurring, the lower the facial beauty and the higher the ugliness perceived. We also found that the shorter the exposure duration, the higher the facial beauty and the lower the ugliness perceived. These results suggest that a positive bias is likely to occur when sufficient temporal information is unavailable, while a negative bias is more likely when image information is insufficient and there is a limited exposure duration. This highlights the importance of both exposure duration and visual clarity in shaping evaluations of facial beauty and ugliness.